Training Paediatric Advanced Life Suport for Nursing Students Using Scenarios, and Learning Outcomes in an Emergency Room During the Clinical Practice - Apóstolo, Jorge Manuel Amado (2013)
Purpose: With increasing numbers of nursing students in Portugal and decreasing numbers of available clinical places, the use of simulation is becoming an integral part of nursing curriculum As part of a Project Group, we have developed at the Nursing School of Coimbra various types and levels of training courses in resuscitation, including courses in Pediatric ALS So, we planned the evaluation of master and bachelor students in clinical practice after a pediatric advanced life suport program Methods: We have used a semi-structured interview and we have selected the emergency units of Pediatric Hospital in Coimbra and a separated Pediatric emergency unit in a General Hospital. This evaluation is focused in ALS when and if the students have participated or have observed emergency situations. Results: We interviewed ten students - four masters and six bachelors All students had been approved in the courses. All of them observed and participated in emergency situations. They confirmed the general validity of training and the safety that they felt when participated in emergency situations. Specially all algoritmes are laearned very well and the work ina team was realized as crtic for the success in the field of resuscitation and in emergency room. Conclusion: Training in Pediatric ALS using scenarios is a response to a clear requirement in the field and the students felt more confidence and safety when they perform in an emergency room.